Energy Innovative Start-ups and Knowledge-based Strategies: The Italian Case - Iazzolino, Gianpaolo; Carolis, Monica De; Clemeno, Paola (International Journal of Energy Economics and Policy, 2019)
The purpose of this paper is to analyze the energy innovative start-ups currently existing in Italy. An investigation on whether those firms are able to implement a knowledge-based strategy (KS) is described: in particular, it is a strategy based on a high investment in qualified human resources and, in general, this is reflected in the fact that the company adopting a KS pays its employees more than the average of other companies belonging to the same sector. Furthermore the ability to generate a return on the investment in knowledge is analyzed. A methodology already proposed in other papers by the same authors was applied in order to identify firms that adopt a KS understanding also the sustainability of such kind of strategy. A discussion on how firms that do not implement a profitable knowledge-based strategy can improve and consolidate their position in terms of knowledge is proposed. Keywords: Energy innovative start-ups, knowledge-based strategy, human capital efficiency, value creation JEL Classifications: M13, M20, M41, O32, O34 DOI: https://doi.org/10.32479/ijeep.7926